A new species of Molineus (Nematoda: Molineidae) parasite of Procyon lotor (Mammalia: Carnivora) in Mexico with a taxonomic key for the species of the genus - Marroquín-Muciño, Mario; Osorio-Sarabia, David; García-Prieto, Luis; Mata-López, Rosario (Zootaxa, 2017)
Molineus lotoris n. sp., parasite of the intestine of the raccoon Procyon lotor collected in Mexico is described and illustrated. The new species can be differentiated from the 27 species included in Molineus by a combination of traits: presence of a prominent and globular cephalic vesicle; spicules with 2 terminal processes, measuring 0.099–0.115 in length and by the number of synlophe ridges at mid-body level of males (17). In addition, a taxonomic key for the species included in Molineus is presented. Finally, some other nematode species collected in raccoons from several localities of Mexico are recorded, including two species not reported for this host in this country: Cameronecator urichi and Aonchotheca (Aonchotheca) putorii.